Automatic Design of Escalator Chain based on SolidWorks - Wang Sheng; Shu Xiangdong; Luo Xiangbin; Wang Xi (Jixie chuandong)
A kind of automatic design of escalator chain is introduced,the design software of Solid Works is chosen. The standard three- dimensional model and drawings are designed,the standardization and design rules are established,then three- dimensional model and engineering drawings could be designed automatically by using the software of Drive Works. Through this method,the design efficiency is improved and some references for designing other products can be offered.